2018
DOI: 10.1021/acs.macromol.8b00176
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Side-Chain Topology on Aggregation of Conjugated Polymers

Abstract: Controlling interchain interactions in conjugated polymers is critical to the development of high performance materials. These interchain interactions are dictated by the aggregation and self-assembly of conjugated polymers in solution and from processing steps, such as thermal annealing, in the solid state. Herein, a macrocyclic benzodithiophene building block for conjugated polymers is developed, and the properties of the resulting polymers are compared to analogous acyclic derivatives. The properties of sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 53 publications
0
21
0
Order By: Relevance
“…For instance, the influence of the chain length, side chains, end groups and regiodefects on the aggregation behavior is now well understood. 9,[15][16][17][18][19] Closely related to the aggregation behavior is the chiral expression. It was found that end groups can be used to tune the chiral response in block copolymers and also the influence of the number of regiodefects was investigated.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the influence of the chain length, side chains, end groups and regiodefects on the aggregation behavior is now well understood. 9,[15][16][17][18][19] Closely related to the aggregation behavior is the chiral expression. It was found that end groups can be used to tune the chiral response in block copolymers and also the influence of the number of regiodefects was investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Because of its planar nature, an increase was observed for high electric conduction in the copolymer series by the function of PAE. 36…”
Section: Results and Discussionmentioning
confidence: 99%
“…This finding agrees with the reported work that the addition of PEO can increase the intrachain molecule aggregation in P3HT film. In the reported work, the role of PEO on the aggregation of P3HT molecules relies on the initial liquid-liquid phase separation, and the liquid-liquid phase separation has been modified by cooling down the fabrication temperatures [12]. Furthermore, decreasing the spin-coating rate of P3HT: PEO films (from 2500 r.p.m.…”
Section: Controlling Of the Molecule Intrachain Ordering In The H-aggmentioning
confidence: 99%
“…It has been demonstrated that molecule aggregation of polymer films can be modified under specific experimental conditions, such as changing the molecular weight [8], doping the insulating material [9], adding the alkyl-chain [10], irradiation by ultraviolet light [11], changing the side-chain structure [12], changing the deposition temperature [13], and changing the transition temperature [14]. Specifically, C. Hellmann et al found that the poly (3-hexylthiophene-2, 5-diyl) (P3HT) backbone can be more planar (J-aggregate behavior) by doping polyethylene oxide (PEO) into P3HT film, and there is a transition from H-aggregate to J-aggregate of P3HT molecules by casting the film below 18 • C [9].…”
Section: Introductionmentioning
confidence: 99%